Cadre Assistance in Utilizing the Infant and Young Child Feeding Counseling Card in Harjosari Village Area - Roziana Roziana; Yolahumaroh Yolahumaroh; Yuliana Arsil (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
The Infant and Young Child Feeding (IYCF) program aims to monitor the growth and development of infants and young children through Early Initiation of Breastfeeding (IMD), exclusive breastfeeding, and appropriate complementary feeding (MP-ASI) until the age of two years. This study aims to evaluate the role and support of Posyandu cadres in Harjosari Village, who are often the closest and most accessible support system for mothers. To enhance their effectiveness, these cadres need improved knowledge and skills in growth monitoring, breastfeeding support, complementary feeding practices, and counseling techniques. The method used in this activity emphasized hands-on practice and participatory discussion to facilitate deeper understanding and application. Based on pre-test and post-test assessments, cadre knowledge increased by 12.5%. Statistical analysis using the paired t-test showed a significant improvement in knowledge (p-value = 0.0001), indicating the effectiveness of the intervention. The findings suggest that with proper training and support, Posyandu cadres can play a more active role in educating mothers. One recommendation is for cadres to initiate practical classes and discussions using infant and young child feeding counseling cards to improve maternal understanding and practices. This approach can contribute to ensuring that feeding practices are implemented correctly and appropriately, supporting optimal child growth and development.